Bài giải mạch P17

Chia sẻ: Tran Thach | Ngày: | Loại File: PDF | Số trang:59

0
65
lượt xem
12
download

Bài giải mạch P17

Mô tả tài liệu
  Download Vui lòng tải xuống để xem tài liệu đầy đủ

Tham khảo tài liệu 'bài giải mạch p17', kỹ thuật - công nghệ, điện - điện tử phục vụ nhu cầu học tập, nghiên cứu và làm việc hiệu quả

Chủ đề:
Lưu

Nội dung Text: Bài giải mạch P17

  1. Chapter 17, Solution 1. (a) This is periodic with ω = π which leads to T = 2π/ω = 2. (b) y(t) is not periodic although sin t and 4 cos 2πt are independently periodic. (c) Since sin A cos B = 0.5[sin(A + B) + sin(A – B)], g(t) = sin 3t cos 4t = 0.5[sin 7t + sin(–t)] = –0.5 sin t + 0.5 sin7t which is harmonic or periodic with the fundamental frequency ω = 1 or T = 2π/ω = 2π. (d) h(t) = cos 2 t = 0.5(1 + cos 2t). Since the sum of a periodic function and a constant is also periodic, h(t) is periodic. ω = 2 or T = 2π/ω = π. (e) The frequency ratio 0.6|0.4 = 1.5 makes z(t) periodic. ω = 0.2π or T = 2π/ω = 10. (f) p(t) = 10 is not periodic. (g) g(t) is not periodic. Chapter 17, Solution 2. (a) The frequency ratio is 6/5 = 1.2. The highest common factor is 1. ω = 1 = 2π/T or T = 2π. (b) ω = 2 or T = 2π/ω = π. (c) f3(t) = 4 sin2 600π t = (4/2)(1 – cos 1200π t) ω = 1200π or T = 2π/ω = 2π/(1200π) = 1/600. (d) f4(t) = ej10t = cos 10t + jsin 10t. ω = 10 or T = 2π/ω = 0.2π.
  2. Chapter 17, Solution 3. T = 4, ωo = 2π/T = π/2 g(t) = 5, 0
  3. 2 bn = (2/2) ∫ (10 − 5t ) sin(nπt )dt 0 2 2 = ∫ (10) sin(nπt )dt – ∫ (5t ) sin(nπt )dt 0 0 2 2 −5 5t = 2 2 sin nπt + cos nπt = 0 + [10/(nπ)](cos 2nπ) = 10/(nπ) n π 0 nπ 0 10 ∞ 1 Hence f(t) = 5 + ∑ sin(nπt ) π n =1 n Chapter 17, Solution 5. T = 2π, ω = 2π / T = 1 T 1 1 a o = ∫ z( t )dt = [1xπ − 2 xπ] = −0.5 T 2π 0 T π 2π 2 1 1 1 π 2 2π an = T ∫ z(t ) cos nωo dt = π ∫ 1cos ntdt − π ∫ 2 cos ntdt = nπ sin ..nt − 0 nπ sin nt π = 0 0 0 π T π 2π  6 2 1 1 1 π 2 2π  , n = odd b n = ∫ z( t ) cos nωo dt = ∫ 1sin ntdt − ∫ 2 sin ntdt = − nπ cos nt 0 + nπ cos nt π =  nπ T π π 0, n = even 0 0 π  Thus, ∞ 6 z( t ) = − 0.5 + ∑ sin nt n =1 nπ n =odd
  4. Chapter 17, Solution 6. 2π T = 2, ωo = =π 2 1 2 1 6 ao = 2 ∫0 y(t )dt = 2 (4x1 + 2x1) = 2 = 3 Since this is an odd function, a n = 0. 2 2 1 2 bn = 2 ∫0 y(t ) sin(nωo t )dt = ∫0 4 sin(nπt )dt + ∫1 2 sin(nπt )dt −4 1 2 2 −4 2 = cos(nπt ) 0 − cos(nπt ) 1 = (cos(nπ) − 1) − (cos(2nπ) − cos(nπ)) nπ nπ nπ nπ 4 2 2 0, n = even = (1 − cos(nπ)) − (1 − cos(nπ)) = (1 − cos(nπ)) = 4 nπ nπ nπ , n = odd nπ 4 ∞ 1 y( t ) = 3 + ∑ sin(nπt ) π n =1 n n = odd Chapter 17, Solution 7. π T = 12, ω = 2π / T = , a0 = 0 6 T 4 10 2 1 a n = ∫ f ( t ) cos nωo dt = [ ∫ 10 cos nπt / 6dt + ∫ (−10) cos nπt / 6dt ] T 6 0 −2 4 10 10 10 10 = 4 sin nπt / 6 − 2 − sin nπt / 6 4 = [2 sin 2nπ / 3 + sin nπ / 3 − sin 5nπ / 3] nπ nπ nπ T 4 10 2 1 b n = ∫ f ( t ) sin nωo dt = [ ∫ 10 sin nπt / 6dt + ∫ (−10) sin nπt / 6dt ] T 6 0 −2 4
  5. 10 10 10 10 =− 4 cos nπt / 6 − 2 + cos nπnt / 6 4 = [cos 5nπ / 3 + cos nπ / 3 − 2 sin 2nπ / 3] nπ nπ nπ ∞ f (t) = ∑ (a n cos nπt / 6 + b n sin nπt / 6) n =1 where an and bn are defined above. Chapter 17, Solution 8. f ( t ) = 2(1 + t ), - 1 < t < 1, T = 2, ωo = 2π / T = π T 1 1 1 1 a o = ∫ f ( t )dt = ∫ 2( t + 1)dt = t 2 + t =2 T 2 0 −1 −1 T 1 1 2 2  1 t 1  an = T ∫ f (t ) cos nωo dt = 2 ∫ 2(t + 1) cos nπtdt = 2 n 2 π 2 cos nπt + nπ sin nπt + nπ sin nπt  = 0     −1 0 −1 T 1 1 2 2  1 t 1  4 bn = T ∫ f (t ) sin nωodt = 2 ∫ 2(t + 1) sin nπtdt = 2 − n 2 π2 sin nπt − nπ cos nπt − nπ cos nπt  = − nπ cos nπ     −1 0 −1 4 ∞ (−1) n f (t) = 2 − ∑ π n =1 n cos nπt Chapter 17, Solution 9. f(t) is an even function, bn=0. T = 8, ω = 2π / T = π / 4 2  10 4 T 2 1 10 ∫ f (t )dt =  ∫ 10 cos πt / 4dt + 0 = ( ) sin πt / 4 2 ao = = = 3.183  4 π π 0 T 0 8 0
  6. T /2 2 2 4 40 ∫ [ 10 cos πt / 4 cos nπt / 4dt +0] = 5∫ [cos πt (n + 1) / 4 + cos πt (n − 1) / 4]dt 8 ∫ an = f (t ) cos nω o dt = T 0 0 0 For n = 1, 2 2 2  a1 = 5∫ [cos πt / 2 + 1]dt = 5 sin πt / 2dt + t  = 10 0 π 0 For n>1, 2 20 π (n + 1)t 20 π (n − 1) 20 π (n + 1) 20 π (n − 1) an = sin + sin = sin + sin π (n + 1) 4 π (n − 1) 4 0 π (n + 1) 2 π (n − 1) 2 10 20 20 10 a2 = sin π + sin π / 2 = 6.3662, a3 = sin 2π + sin π = 0 π π 4π π Thus, a 0 = 3.183, a1 = 10, a 2 = 6.362, a3 = 0, b1 = 0 = b2 = b3 Chapter 17, Solution 10. T = 2, ωo = 2π / T = π T 1 1 1 1  4e − jnπt 1 2e − jnπt 2  h ( t )e − jnωo t dt =  ∫ 4e − jnπt dt + ∫ (−2)e − jnπt dt  =  2 T∫ cn =  2 − jnπ 0 − − jnπ 1  2 0  1      0 [ ]  6j j j − , n = odd cn = 4e − jπn − 4 − 2e − j2nπ + 2e − jnπ = [6 cos nπ − 6] =  nπ , 2nπ 2nπ  0, n = even  Thus, ∞  − j6  jnπt f (t ) = ∑  e n =−∞  nπ  n =odd
  7. Chapter 17, Solution 11. T = 4, ω o = 2π / T = π / 2 T 1 1 0 c n = ∫ y( t )e − jnωo t dt =  ∫ ( t + 1)e − jnπt / 2 dt + ∫ (1)e − jnπt / 2 dt  1 T  −1 4 0   0 1  e − jnπt / 2 2 − jnπt / 2 0 2 − jnπt / 2 1  cn =  2 2 (− jnπt / 2 − 1) − e − −1 jnπ e 0 4 − n π / 4  jnπ   1 4 2 4 jnπ / 2 2 jnπ / 2 2 − jnπ / 2 2  =  2 2 − jnπ + 2 2 e ( jnπ / 2 − 1) + e − e + 4 n π n π jnπ jnπ jnπ   But e jnπ / 2 = cos nπ / 2 + j sin nπ / 2 = j sin nπ / 2, e − jnπ / 2 = cos nπ / 2 − j sin nπ / 2 = − j sin nπ / 2 1 cn = [1 + j( jnπ / 2 − 1) sin nπ / 2 + nπ sin nπ / 2] n 2π2 ∞ 1 y( t ) = ∑ 2 2 [1 + j( jnπ / 2 − 1) sin nπ / 2 + nπ sin nπ / 2]e jnπt / 2 n = −∞ n π Chapter 17, Solution 12. A voltage source has a periodic waveform defined over its period as v(t) = t(2π - t) V, for all 0 < t < 2π Find the Fourier series for this voltage. v(t) = 2π t – t2, 0 < t < 2π, T = 2π, ωo = 2π/T = 1 ao = T 1 2π 1 2π 4π 3 2π 2 (1/T) ∫ f ( t )dt = ∫0 (2πt − t )dt = 2π (πt − t / 3) 2 2 3 = (1 − 2 / 3) = 0 2π 0 2π 3
  8. 2π 2 T 1  2π 2πt  an = ∫ (2πt − t 2 ) cos(nt )dt =  2 cos(nt ) + sin(nt ) T 0 π n n 0 − 1 πn 3 [ 2nt cos(nt ) − 2 sin(nt ) + n 2 t 2 sin( nt ) ] 2π 0 2 1 −4 = (1 − 1) − 3 4nπ cos(2πn ) = 2 n 2 πn n 2 T 1 ∫0 (2nt − t ) sin(nt )dt = π ∫ (2nt − t ) sin(nt )dt 2 2 bn = T 2n 1 π 1 2π = (sin(nt ) − nt cos(nt )) 0 − 3 (2nt sin(nt ) + 2 cos(nt ) − n 2 t 2 cos(nt )) π n 2 πn 0 − 4 π 4π = + =0 n n 2π 2 ∞ 4 Hence, f(t) = − ∑ 2 cos(nt ) 3 n =1 n Chapter 17, Solution 13. T = 2π, ωo = 1 T 1 π 2π ao = (1/T) ∫ h( t )dt = [ ∫ 10 sin t dt + ∫ 20 sin( t − π) dt ] 0 2π 0 π = 1 2π [ π 2π − 10 cos t 0 − 20 cos( t − π) π = 30 π ] T an = (2/T) ∫ h( t ) cos(nω t )dt 0 o = [2/(2π)]  ∫ 10 sin t cos( nt )dt + 20 sin( t − π) cos( nt )dt  π 2π 0  ∫π   Since sin A cos B = 0.5[sin(A + B) + sin(A – B)] sin t cos nt = 0.5[sin((n + 1)t) + sin((1 – n))t] sin(t – π) = sin t cos π – cost sin π = –sin t sin(t – π)cos(nt) = –sin(t)cos(nt)
  9. 1  π 10∫ [sin([1 + n ]t ) + sin([1 − n ]t )]dt − 20∫ [sin([1 + n ]t ) + sin([1 − n ]t )]dt  2π an = 2π  0  π   5  cos([1 + n ]t ) cos([1 − n ]t )  π  2 cos([1 + n ]t ) 2 cos([1 − n ]t )  2 π  =  − −  + +   π   1+ n 1− n 0  1+ n 1− n π   5  3 3 3 cos([1 + n ]π) 3 cos([1 − n ]π)  an = π 1 + n + 1 − n −  1+ n − 1− n   But, [1/(1+n)] + [1/(1-n)] = 1/(1–n2) cos([n–1]π) = cos([n+1]π) = cos π cos nπ – sin π sin nπ = –cos nπ an = (5/π)[(6/(1–n2)) + (6 cos(nπ)/(1–n2))] = [30/(π(1–n2))](1 + cos nπ) = [–60/(π(n–1))], n = even = 0, n = odd T bn = (2/T) ∫ h ( t ) sin nωo t dt 0 π 2π = [2/(2π)][ ∫ 10 sin t sin nt dt + ∫ 20( − sin t ) sin nt dt 0 π But, sin A sin B = 0.5[cos(A–B) – cos(A+B)] sin t sin nt = 0.5[cos([1–n]t) – cos([1+n]t)] π bn = (5/π){[(sin([1–n]t)/(1–n)) – (sin([1+n]t)/ (1 + n )] 0 2π + [(2sin([1-n]t)/(1-n)) – (2sin([1+n]t)/ (1 + n )] π } 5  sin([1 − n ]π) sin([1 + n ]π)  = π −  1− n + 1+ n  = 0  30 60 ∞ cos( 2kt ) Thus, h(t) = π − ∑ π k = 1 ( 4k 2 − 1)
  10. Chapter 17, Solution 14. Since cos(A + B) = cos A cos B – sin A sin B. ∞  10 10  f(t) = 2 + ∑  3 cos(nπ / 4) cos( 2nt ) − 3 sin(nπ / 4) sin( 2nt )  n =1  n + 1 n +1  Chapter 17, Solution 15. (a) Dcos ωt + Esin ωt = A cos(ωt - θ) where A = D 2 + E 2 , θ = tan-1(E/D) 16 1 A = + 6 , θ = tan-1((n2+1)/(4n3)) ( n + 1) 2 2 n ∞ 16 1  −1 n + 1  2 f(t) = 10 + ∑ + ( n 2 + 1) 2 n 6 cos 10nt − tan   4n 3  n =1   (b) Dcos ωt + Esin ωt = A sin(ωt + θ) where A = D 2 + E 2 , θ = tan-1(D/E) ∞ 16 1  4n 3  f(t) = 10 + ∑ + ( n 2 + 1) 2 n 6 sin 10nt + tan  −1  n2 + 1  n =1   Chapter 17, Solution 16. If v2(t) is shifted by 1 along the vertical axis, we obtain v2*(t) shown below, i.e. v2*(t) = v2(t) + 1. v2*(t) 2 1 t -2 -1 0 1 2 3 4 5
  11. Comparing v2*(t) with v1(t) shows that v2*(t) = 2v1((t + to)/2) where (t + to)/2 = 0 at t = -1 or to = 1 Hence v2*(t) = 2v1((t + 1)/2) But v2*(t) = v2(t) + 1 v2(t) + 1 = 2v1((t+1)/2) v2(t) = -1 + 2v1((t+1)/2) 8   t + 1 1  t + 1 1  t + 1  = -1 + 1 − cos π 2  + 9 cos 3π 2  + 25 cos 5π 2  +  π2         8   πt π  1  3πt 3π  1  5πt 5π   v2(t) = − cos 2 + 2  + 9 cos 2 + 2  + 25 cos 2 + 2  +  π2         8   π t  1  3 πt  1  5 πt   v2(t) = − sin 2  + 9 sin 2  + 25 sin 2  +  π2         Chapter 17, Solution 17. We replace t by –t in each case and see if the function remains unchanged. (a) 1 – t, neither odd nor even. (b) t2 – 1, even (c) cos nπ(-t) sin nπ(-t) = - cos nπt sin nπt, odd (d) sin2 n(-t) = (-sin πt)2 = sin2 πt, even (e) e t, neither odd nor even.
  12. Chapter 17, Solution 18. (a) T = 2 leads to ωo = 2π/T = π f1(-t) = -f1(t), showing that f1(t) is odd and half-wave symmetric. (b) T = 3 leads to ωo = 2π/3 f2(t) = f2(-t), showing that f2(t) is even. (c) T = 4 leads to ωo = π/2 f3(t) is even and half-wave symmetric. Chapter 17, Solution 19. This is a half-wave even symmetric function. ao = 0 = bn, ωo = 2π/T π/2 4 T/2  4t  an = T ∫0 1 − T  cos(nωo t )dt   = [4/(nπ)2](1 − cos nπ) = 8/(n2π2), n = odd = 0, n = even 8 ∞ 1  nπt  f (t) = π2 ∑ n = odd n 2 cos  2   Chapter 17, Solution 20. This is an even function. bn = 0, T = 6, ω = 2π/6 = π/3 2 2 2 ( 4 t − 4)dt ∫ 4 dt  T/2 3 ao = T ∫ 0 f ( t )dt = 6  ∫1  2  
  13. 1 2 ( 2 t − 4 t ) + 4(3 − 2) = 2 2 = 3  1   4 T/4 an = T ∫ 0 f ( t ) cos( nπt / 3)dt 2 3 = (4/6)[ ∫ ( 4 t − 4) cos( nπt / 3)dt + ∫ 4 cos( nπt / 3)dt ] 1 2 2 3 16  9  nπt  3t  nπt  3  nπt  16  3  nπt  =  n 2 π 2 cos 3  + nπ sin 3  − nπ sin 3  + 6  nπ sin 3  6       1    2 = [24/(n2π2)][cos(2nπ/3) − cos(nπ/3)] 24 ∞ 1   2πn   πn    nπt  Thus f(t) = 2 + ∑ π 2 n =1 n2 cos 3  − cos 3   cos 3         At t = 2, f(2) = 2 + (24/π2)[(cos(2π/3) − cos(π/3))cos(2π/3) + (1/4)(cos(4π/3) − cos(2π/3))cos(4π/3) + (1/9)(cos(2π) − cos(π))cos(2π) + -----] = 2 + 2.432(0.5 + 0 + 0.2222 + -----) f(2) = 3.756 Chapter 17, Solution 21. This is an even function. bn = 0, T = 4, ωo = 2π/T = π/2. f(t) = 2 − 2t, 0
  14. = [8/(π2n2)][1 − cos(nπ/2)] 1 ∞ 8   nπ    nπt  f(t) = 2 + ∑n π 2 2 1 − cos 2   cos 2      n=1  Chapter 17, Solution 22. Calculate the Fourier coefficients for the function in Fig. 16.54. f(t) 4 t -5 -4 -3 -2 -1 0 1 2 3 4 5 Figure 17.61 For Prob. 17.22 This is an even function, therefore bn = 0. In addition, T=4 and ωo = π/2. 2 T2 2 1 2 1 ao = T ∫ 0 f ( t )dt = 4 ∫0 4tdt = t 0 = 1 4 T2 4 1 an = T ∫ 0 f ( t ) cos(ωo nt )dt = 4 ∫0 4 t cos( nπt / 2)dt 1  4 2t  = 4  2 2 cos( nπt / 2) + sin( nπt / 2) n π nπ 0 16 8 an = (cos( nπ / 2) − 1) + sin( nπ / 2) n π 2 2 nπ Chapter 17, Solution 23. f(t) is an odd function. f(t) = t, −1< t < 1 ao = 0 = an, T = 2, ωo = 2π/T = π
  15. 4 T/2 4 1 bn = T ∫ 0 f ( t ) sin( nωo t )dt = 2 ∫0 t sin( nπt )dt 2 = [sin(nπt ) − nπt cos(nπt )] 10 n π 2 2 = −[2/(nπ)]cos(nπ) = 2(−1)n+1/(nπ) 2 ∞ ( −1) n + 1 f(t) = π ∑ n =1 n sin( nπt ) Chapter 17, Solution 24. (a) This is an odd function. ao = 0 = an, T = 2π, ωo = 2π/T = 1 4 T/2 bn = T ∫0 f ( t ) sin(ωo nt )dt f(t) = 1 + t/π, 0
  16. ∞ 2 (c) f(t) = ∑ nπ [1 − 2 cos(nπ)] sin(nt ) π n =1 ∞ 2 f(π/2) = ∑ nπ [1 − 2 cos(nπ)] sin(nπ / 2) π n =1 For n = 1, f1 = (2/π)(1 + 2) = 6/π For n = 2, f2 = 0 For n = 3, f3 = [2/(3π)][1 − 2cos(3π)]sin(3π/2) = −6/(3π) For n = 4, f4 = 0 For n = 5, f5 = 6/(5π), ---- Thus, f(π/2) = 6/π − 6/(3π) + 6/(5π) − 6/(7π) --------- = (6/π)[1 − 1/3 + 1/5 − 1/7 + --------] f(π/2) ≅ 1.3824 which is within 8% of the exact value of 1.5. (d) From part (c) f(π/2) = 1.5 = (6/π)[1 − 1/3 + 1/5 − 1/7 + - - -] (3/2)(π/6) = [1 − 1/3 + 1/5 − 1/7 + - - -] or π/4 = 1 − 1/3 + 1/5 − 1/7 + - - - Chapter 17, Solution 25. This is an odd function since f(−t) = −f(t). ao = 0 = an, T = 3, ωo = 2π/3. 4 T/2 4 1 bn = T ∫ 0 f ( t ) sin( nωo t )dt = 3 ∫0 t sin(2πnt / 3)dt
  17. 1 4 9  2πnt  3t  2πnt  =  4π 2 n 2 sin 3  − 2nπ cos 3  3     0 4 9  2 πn  3  2 πn   =  4π 2 n 2 sin 3  − 2nπ cos 3  3     ∞  3  2 πn  2  2π n    2π t  f(t) = ∑ π n 2 2 sin −  3  nπ cos   sin  3   3   n =1  Chapter 17, Solution 26. T = 4, ωo = 2π/T = π/2 1 T 1 1 f ( t )dt =  ∫ 1 dt + 2 dt + ∫ 1 dt  = 1 3 4 T ∫0 ∫ ao = 40  1 3   2 T T ∫0 an = f ( t ) cos( nωo t )dt 2 2 2 cos( nπt / 2)dt + ∫ 1 cos( nπt / 2)dt  3 4 4  ∫1 ∫ an = 1 cos( nπt / 2)dt +  2 3   2 nπt 2 4 nπt 3 2 nπt  4 = 2  sin + sin + sin   nπ  2 1 nπ 2 2 nπ 2 3 4  3nπ nπ  = nπ sin 2 − sin 2    2 T T ∫0 bn = f ( t ) sin( nωo t )dt 2 2 nπt 3 nπt 4 nπt  =  ∫1 1 sin 2 dt + 4 ∫ 2 2 sin 2 dt + ∫ 3 1 sin 2 dt    2 nπt 2 4 nπt 3 2 nπt  4 = 2− cos − cos − cos   nπ  2 1 nπ 2 2 nπ 2 3
  18. 4 = [cos(nπ) − 1] nπ Hence f(t) = ∞ 4 1+ ∑ nπ [(sin( 3nπ / 2) − sin(nπ / 2)) cos( nπt / 2) + (cos( nπ) − 1) sin(nπt / 2)] n =1 Chapter 17, Solution 27. (a) odd symmetry. (b) ao = 0 = an, T = 4, ωo = 2π/T = π/2 f(t) = t, 0 < t < 1 = 0, 1
  19. Chapter 17, Solution 28. This is half-wave symmetric since f(t − T/2) = −f(t). ao = 0, T = 2, ωo = 2π/2 = π 4 T/2 4 1 an = T ∫ 0 f ( t ) cos( nωo t )dt = 2 ∫0 ( 2 − 2 t ) cos( nπt )dt 1 1 1 t  = 4  sin( nπt ) − 2 2 cos( nπt ) − sin( nπt )  nπ n π nπ 0 = [4/(n2π2)][1 − cos(nπ)] = 8/(n2π2), n = odd 0, n = even 1 bn = 4 ∫ (1 − t ) sin( nπt )dt 0 1  1 1 t  = 4 − cos( nπt ) − 2 2 sin( nπt ) + cos( nπt )  nπ n π nπ 0 = 4/(nπ), n = odd ∞  8 4  f(t) = ∑n  k =1 π 2 2 cos( nπt ) + nπ sin(nπt )  , n = 2k − 1  Chapter 17, Solution 29. This function is half-wave symmetric. T = 2π, ωo = 2π/T = 1, f(t) = −t, 0 < t < π 2 2 [cos(nt ) + nt sin(nt )] 0 = 4/(n2π) π π For odd n, an = T ∫ 0 ( − t ) cos( nt )dt = − n π 2 2 2 [sin(nt ) − nt cos(nt )] 0 = −2/n π π bn = π ∫ 0 ( − t ) sin( nt )dt = − n π 2
  20. Thus, ∞  2 1  f(t) = 2∑  2 cos( nt ) − sin(nt ) , n = 2k − 1 k =1  n π n  Chapter 17, Solution 30. T/2 1 1  T/2 T/2  cn = ∫ f ( t )e − jnωo t dt =  ∫−T / 2 f ( t ) cos nω o tdt − j∫−T / 2 f ( t ) sin nω o tdt  (1) T T  −T / 2 (a) The second term on the right hand side vanishes if f(t) is even. Hence T/2 2 cn = T ∫ f (t ) cos nωo tdt 0 (b) The first term on the right hand side of (1) vanishes if f(t) is odd. Hence, T/2 j2 cn = − T ∫ f (t ) sin nωo tdt 0 Chapter 17, Solution 31. 2π 2π If h ( t ) = f (αt ), T' = T / α  → ωo ' = = = αωo T' T / α T' T' 2 2 an '= T' ∫ h (t ) cos nωo ' tdt = T' ∫ f (αt ) cos nωo ' tdt 0 0 Let αt = λ, , d t = dλ / α , αT ' = T T 2α T ∫ an '= f (λ) cos nωo λdλ / α = a n 0 Similarly, bn ' = bn
Đồng bộ tài khoản